GTn Repeat Microsatellite Instability in Uterine Fibroids - Kénémé, Bineta; Sembène, Mbacké (Frontiers in Genetics, 2019)
Background: Type I collagen is a triple helix structure with two α1 and one α2 chains. Coordinated biosynthesis of α1 and α2 subunits is very important for tissue morphogenesis, growth, and repair. In contrast, abnormal deposition in response to proinflammatory cytokines is associated with organ dysfunction. In humans, COL1A2 contains 2 microsatellite loci: one located at the 5'-flanking region is composed of poly CA and poly CG, the other located in the 1st intron is constituted of poly GT. Expression of COL1A2 has been noted in gastric cancer and was positively correlated with degree of invasion and metastases. But no genetic study taking into account polymorphism of COL1A2 in uterine fibroids has been undertaken. Methods: In this study, repeated dinucleotide GTn of intron 1 COL1A2 was highlighted in 55 patients with uterine fibroids (UF). Clinical and pathological data were obtained from patient’s records and other parameters were recorded. Mutation Surveyor version 5.0.1, DnaSP version 5.10, MEGA version 7.0.26 and Arlequin version 3.5.1.3 were used to determine genetics parameters. To estimate genetic variation according to epidemiological parameters, index of genetic differentiation (Fst) and genetic structure (AMOVA) were determined with Arlequin version. Results: Based on reference microsatellite pattern (GT)14CT(GT)3CT(GT)3, 15 haplotypes were found. Among the 15 haplotypes, 12 have a mutation at position 2284C>G and 7 at position 2292C>G. Insertions of repeated dinucleotide GTn were found on 3 haplotypes against 8 haplotypes in which they are deletions. Intron 1 of COL1A2 gene exhibits high genetic diversity in uterine fibroids with 35.34% polymorphic sites, 95.74% of which were parsimoniously variable and an average number of nucleotide difference of 10.442, which reflects an important genetic variability. According to epidemiological parameters, our results showed, for the first time, a genetic structuring of uterine fibroids according to ethnicity, marital status, use of contraception, diet and physical activity; beyond confirming the involvement dinucleotide length polymorphism GTn in occurrence of uterine fibroids in Senegalese women. Conclusion: results obtained open up avenues for understanding the mechanisms involved in the racial variation in the prevalence of uterine fibroids as well as the predisposing factors.